Prognostic factors and outcome of ABVD chemotherapy in childhood Hodgkin Iymphoma: A single center experience (Annals of Medical Research, 2021)
Aim: The aim was to analyze the outcome of pediatric Hodgkin lymphoma patients treated with doxorubicin, bleomycin, vinblastine, and dacarbazine (ABVD) chemotherapy + adjuvant radiotherapy according to the risk groups and determine the adverse prognostic factors affecting survival in Hodgkin lymphoma.Material and Methods: A retrospective study was performed on 52 pediatric patients with Hodgkin lymphoma who were treated with ABVD between 1997 and 2018. Patients with early-stage favorable disease received 4 cycles of ABVD + radiotherapy. Early-stage unfavorable and advanced-stage patients received 6 cycles of ABVD + radiotherapy.Results: Thirty (57.7%) boys and 22 (42.3%) girls were included in the study. The median age of the patients was 9 years and 3 months (1 year and 10 month – 17 years and 7 months). Overall survival rate was 94.2% and the mean survival time was 19.5±0.70 (95% CI, 18.1 - 20.9) years. The mean event-free survival time was 9.5±6.5 years. Overall survival rate was 90%, and the mean event-free survival time was 8.2±6.1 years in early-stage favorable disease. Overall survival rate was 100%, and the mean event-free survival time was 1.9±7.0 years in early-stage unfavorable disease. Overall survival rate was 94.1 %, and the mean event-free survival time was 8.9±6.3 years in advanced-stage disease. Presence of bulky disease, nodular sclerosing histologic subtype and leukocytosis had a negative prognostic effect on relapse and bulky disease had adverse effect on overall survival (p0.05). Conclusion: Four courses of ABVD chemotherapy + radiotherapy (IFRT or ISRT) in early-stage favorable patients and 6 courses of ABVD chemotherapy + radiotherapy (IFRT or ISRT) in both early-stage unfavorable and advanced-stage Hodgkin lymphoma patients benefited from promising outcomes in terms of OS and FFS. Presence of bulky disease, nodular sclerosing histologic subtype and leukocytosis have adverse prognostic effects on relapse and presence of bulky disease have adverse effect on OS.Keywords: Hodgkin lymphoma; prognosis; overall survival.
Keywords: Hodgkin lymphoma; prognosis; overall survival.